Critical Analysis of Health Communication, Technological Interventions, And Behavioral Change in Public Health - Hefshan, Saleh Dafer Taleb; Al Abbas, Rasheed Hadi Mohsen; Al Abbas, Saleh Hadi Ali; Al Alabbas, Ibrahim Hadi Ali; Al Rashah, Abdul Mohsen Yahya Mohsen; Alrashah, Ahmed Yahya Mohsen; Alsagoor, Mohsen Mubark Ali; Al Abbas, Mahdi Saleh Shettah; Alshhai, Ali Mohsen Saeed; alshetah, AlHassan rashed mahde (Journal of Ecohumanism, 2024)
This review synthesizes a critical appraisal of health communication, technology, and behavior change interventions for public health. Looking at the current and emerging trends in global health communication, the following factors become a focus in managing health crises: In this paper, the different methods of communication used in public health communication interventions are discussed, an analysis of the role of technology in improving health is discussed, and finally, the effectiveness of behavior change theories in promoting healthier behaviors is examined. This study, therefore, provides an overview of the literature to identify possibilities and constraints as far as using these tools is concerned in enhancing public health. Seamless integration of these components is crucial in program design when adopting population health approaches to disease prevention, health promotion, and health enhancement among different populations.